Fish scale containing alginate dialdehyde-gelatin bioink for bone tissue engineering. (15th February 2023) - Kara Özenler, Aylin; Distler, Thomas; Tihminlioglu, Funda; Boccaccini, Aldo R
Abstract: The development of biomaterial inks suitable for biofabrication and mimicking the physicochemical properties of the extracellular matrix is essential for the application of bioprinting technology in tissue engineering (TE). The use of animal-derived proteinous materials, such as jellyfish collagen, or fish scale (FS) gelatin (GEL), has become an important pillar in biomaterial ink design to increase the bioactivity of hydrogels. However, besides the extraction of proteinous structures, the use of structurally intact FS as an additive could increase biocompatibility and bioactivity of hydrogels due to its organic (collagen) and inorganic (hydroxyapatite) contents, while simultaneously enhancing mechanical strength in three-dimensional (3D) printing applications. To test this hypothesis, we present here a composite biomaterial ink composed of FS and alginate dialdehyde (ADA)-GEL for 3D bioprinting applications. We fabricate 3D cell-laden hydrogels using mouse pre-osteoblast MC3T3-E1 cells. We evaluate the physicochemical and mechanical properties of FS incorporated ADA-GEL biomaterial inks as well as the bioactivity and cytocompatibility of cell-laden hydrogels. Due to the distinctive collagen orientation of the FS, the compressive strength of the hydrogels significantly increased with increasing FS particle content. Addition of FS also provided a tool to tune hydrogel stiffness. FS particles were homogeneously incorporated into the hydrogels. Particle-matrix integration was confirmed via scanning electron microscopy. FS incorporation in the ADA-GEL matrix increased the osteogenic differentiation of MC3T3-E1 cells in comparison to pristine ADA-GEL, as FS incorporation led to increased ALP activity and osteocalcin secretion of MC3T3-E1 cells. Due to the significantly increased stiffness and supported osteoinductivity of the hydrogels, FS structure as a natural collagen and hydroxyapatite source contributed to the biomaterial ink properties for bone engineering applications. Our findings indicate that ADA-GEL/FS represents a new biomaterial ink formulation with great potential for 3D bioprinting, and FS is confirmed as a promising additive for bone TE applications.